Characterization of cryptic splicing in germline PTEN intronic variants in Cowden syndrome. Issue 10 (17th July 2017) - Chen, Hannah Jinlian; Romigh, Todd; Sesock, Kaitlin; Eng, Charis
Abstract : Different cryptic splicing in germline PTEN intronic variants in Cowden Syndrome characterized. PTEN intronic variants that result in splice changes decrease the PTEN protein level. Abstract: Germline mutations in the tumor‐suppressor gene PTEN predispose to subsets of Cowden syndrome (CS), Bannayan–Riley–Ruvalcaba syndrome, and autism. Evidence‐based classification of PTEN variants as either deleterious or benign is urgently needed for accurate molecular diagnosis and gene‐informed genetic counseling. We studied 34 different germline PTEN intronic variants from 61 CS patients, characterized their PTEN mRNA processing, and analyzed PTEN expression and downstream readouts of P‐AKT and P‐ERK1/2. While we found that many mutations near splice junctions result in exon skipping, we also identified the presence of cryptic splicing that resulted in premature termination or a shift in isoform usage. PTEN protein expression is significantly lower in the group with splicing changes while P‐AKT, but not P‐ERK1/2, is significantly increased. Our observations of these PTEN intronic variants should contribute to the determination of pathogenicity of PTEN intronic variants and aid in genetic counseling.